Associations between surrogate insulin resistance indexes and osteoarthritis: NHANES 2003–2016 - Youmian Lan; Qiongbing Zheng; Meijing Li; Jiexin Chen; Dongyang Huang; Ling Lin (Scientific Reports)
Abstract Insulin resistance (IR) and abdominal obesity are key in osteoarthritis (OA) development. The triglyceride glucose (TyG) index, along with indicators such as the visceral adiposity index (VAI), and lipid accumulation product (LAP), are increasingly used to measure IR. This study aims to explore the associations between surrogate IR indexes and OA, assessing their diagnostic efficacy within American populations. This study included 14,715 adults from the National Health and Nutrition Examination Survey 2003–2016. Logistic regression models and restricted cubic spline were used to explore the relationship between surrogate IR indexes and OA. Receiver operating characteristic curves were constructed to assess the diagnostic efficacy of these indices, with the area under the curve (AUC) as the metric. TyG, glucose triglyceride-waist circumference (TyG-WC), glucose triglyceride-body mass index (TyG-BMI), glucose triglyceride-waist height ratio (TyG-WHtR), VAI and LAP were significantly and positively associated with the prevalence of OA (all p < 0.01). After adjusting for various potential confounders, TyG-WC, TyG-BMI, TyG-WHtR and LAP remained significantly correlated with the prevalence of OA. Furthermore, restricted cubic spline revealed a nonlinear association between TyG-BMI, TyG-WHtR and LAP (all P-non-linear < 0.05). Receiver operating characteristic curves indicated that TyG-WHtR (AUC 0.633) demonstrated more robust diagnostic efficacy. Additionally, the sensitivity analysis produced results consistent with the primary findings. TyG and its combination with obesity indicators and LAP, are positively associated with the prevalence of OA, with TyG-WHtR showing the highest diagnostic efficacy.